Avaliação do potencial antimicrobiano do decocto da folha do cajá (Spondias mombin L) na prevenção da mastite bovina - Fernandes, Fernando da Costa (Universidade Federal Rural do Semi-Árido, 2019)
Studies verified the use of Spondias mombin L. as antimicrobial which shows that its extract may have antiseptic action. The aim of this study was to verify the in vivo antimicrobial action of Spondias mombin L. leaves decoct in dairy cattle matrices. This work was carried out with animals belonging to producers of the rural area of the city of Mossoro / RN, collections performed during the months of August / 2018 to March / 2019. Following a principle of randomness, a total of 32 lactating females were selected, which remained in this condition for a period of at least 28 days, corresponding to the duration of the treatment. The cows were separated into four treatment groups: I - iodine (positive control); II - water (negative control); III - lactic acid (used by the producer) and IV - decoction of cajá leaves (alternative option). In each group of cows, immersion treatments were applied to the teats with the corresponding product, using disinfection cups for post-dipping tit. Each product was applied onto the tit and allowed to act for a period of 10 minutes, so that the collection, friction of sterile swab on the lateral surface of each teat was collected. Applications were made twice a day by producers for twenty-eight consecutive days. Then, each swab was placed in an identified test tube, stored in a refrigerated isothermal box and brought for analysis to the Veterinary Microbiology Laboratory located at UFERSA, where after processing it went to the mesophilic counting technique. The general state of the mammary gland of the animals submitted to the experiment was also evaluated for the presence of clinical changes causes by the presence of mastitis as; swelling and pain in the gland, edema, increased temperature, secrection, blood, lumps or other changes in milk. The decoction was submitted to phytochemical evaluation to evaluate possible bioactive substances that explain its antiseptic action. As for the statistical analysis of the experimental data obtained were submitted to analysis of variance, and the comparison between the means of the treatments will be done by the Tukey test, at 5% probability, using the statistical program Sisvar®. We performed regression analysis and adjustment procedures of response curves for each variable as a function of the days application through the 'Table Curve' software. There was a tendency to reduce the number of UFC’s in cows treated with extract cajá and iodine, obtaining a mean of 1026.7 and 1025.5 UFC / cm², respectively. Different behavior was observed in the animals that used lactic acid and water, obtaining averages of 1210.1 and 1663.8 UFC / cm², respectively. The results of this study confirm the effectiveness of Spondia monbim extract as a potential antibacterial agent. Concluding that the decoction of the leaves of Spondia mombin L. presented a good alternative antiseptic potential compared to the conventional products used in post-dipping. It was also possible to identify active principles through phytochemical analysis such as phenols, tannins, flavonols, flavones, flavonones, xanthones, steroids, triterpenoids, saponins and quinones. The observation of pathological signs, indicating the presence of mastitis in the tits of the animals submitted to the experiment, observed that; there were no clinical alterations in the animals treated with iodine and decoction of cajá, since water and lactic acid were not able to inhibit the presence of clinical mastitis. Symptoms such as hyperemia, edema, secretion, heat and pain in the ceilings of the patients were observed. animals subjected to such treatments.
Monografia
Keywords: Ordenha; Pós-dipping; Antisséptico; Produto natural; Alternativa; Milking; Post-dipping; Antiseptic; Natural product; Alternative; CIENCIAS AGRARIAS::MEDICINA VETERINARIA